Penyaluran Zakat untuk Penanganan Dampak Covid-19 dalam Perspektif Hukum Islam (Analisis Pendapat Para Ulama Fikih) - Askar Patahuddin; Azwar Azwar; Muh. Syukur S. (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine the law of distributing zakat in the prevention of Covid-19 based on the perspective of Islamic law. This research is a type of qualitative research that focuses on the study of texts (library research) with a normative and historical approach. The results of the study show that the law for distributing zakat is in tackling or handling the impact of Covid-19, such as the allocation of consumptive zakat on the procurement of basic needs, medicines, Personal Protective Equipment (PPE) clothing for medical personnel, disinfectants needed by officers or volunteers, and others, are mubah (permissible). This law of permissibility is based on the study of the verses of the Qur'an, hadith and the opinions of scholars. However, this permit still has to prioritize the poor in meeting their basic needs in the form of zakat distribution, both in cash and in kind.